KSHV LANA acetylation-selective acidic domain reader sequence mediates virus persistence - Juillard, Franceline (2021)
Viruses modulate biochemical cellular pathways to permit infection. A recently described mechanism mediates selective protein interactions between acidic domain readers and unacetylated, lysine-rich regions, opposite of bromodomain function. Kaposi´s sarcoma (KS)-associated herpesvirus (KSHV) is tightly linked with KS, primary effusion lymphoma, and multicentric Castleman’s disease. KSHV latently infects cells, and its genome persists as a multicopy, extrachromosomal episome. During latency, KSHV expresses a small subset of genes, including the latency-associated nuclear antigen (LANA), which mediates viral episome persistence. Here we show that LANA contains two tandem, partially overlapping, acidic domain sequences homologous to the SET oncoprotein acidic domain reader. This domain selectively interacts with unacetylated p53, as evidenced by reduced LANA interaction after overexpression of CBP, which acetylates p53, or with an acetylation mimicking carboxyl-terminal domain p53 mutant. Conversely, the interaction of LANA with an acetylation-deficient p53 mutant is enhanced. Significantly, KSHV LANA mutants lacking the acidic domain reader sequence are deficient for establishment of latency and persistent infection. This deficiency was confirmed under physiological conditions, on infection of mice with a murine gammaherpesvirus 68 chimera expressing LANA, where the virus was highly deficient in establishing latent infection in germinal center B cells. Therefore, LANA’s acidic domain reader is critical for viral latency. These results implicate an acetylation-dependent mechanism mediating KSHV persistence and expand the role of acidic domain readers.